Ladinos with Ladinos, Indians with Indians : Land, Labor, and Regional Ethnic Conflict in the Making of Guatemala. - Reeves, René (Stanford University Press, 2006)
In the late 1830s, an uprising of mestizos and Maya destroyed Guatemala's Liberal government. Liberal partisans were unable to retake the state until 1871. In contrast to the late 1830s, they met only sporadic resistance. This work confronts this paradox of Guatemala's nineteenth century by focusing on the rural folk of the western highlands.